Influence of reactive power compensation from PV systems on electrical grid - Raghad Adeeb Othman; Omar Sharaf Al-Deen Yehya Al-Yozbaky (Institute of Advanced Engineering and Science, 2023)
The rising electricity consumption, rapid fossil fuel depletion, and a higher shift to the use of renewable or green energy resources have increased the need to integrate renewable and distributed energy resources (DERs), like solar photovoltaic (PV) energy to power the utility grids. In this study, the researchers have determined the effect of PV inverters to offer reactive power to an adapted IEEE 13-node distribution network. Power flow analyses were conducted on MATLAB/Simulink for various reactive power modes of PV inverters to show the effect of the reactive power on the regulation of grid voltage, reduced the total harmonic distortion (THD), and maintain the power factor so as to improve the ability of the system to handle power. The result shows that using a 400 KW PV system in a bus (675) led to a reduction in the power generated from the generator by 11%, and the use of the reactive power capability of PV inverters on-site improved the voltage profile significantly. as well, reduced the voltage THD by 27.09% when injected with reactive power, reduce the current THD by 77.39% When absorbing reactive power, and improved the power factor on-site.